High-thermal-conductivity aluminum oxide ceramic and preparation process thereof

By using nano-scale alumina powder and micro-scale alumina fibers, combined with beryllium-zirconium composite fibers, a three-dimensional thermal conductivity network and composite solid solution are formed, the problem of insufficient thermal conductivity of traditional alumina ceramics is solved, and the thermal conductivity of the ceramics is significantly improved and mechanical properties, suitable for heat dissipation and high temperature applications of high-performance electronic devices.

CN119462104AActive Publication Date: 2025-02-18SUZHOU JINGCI SUPER HARD MATERIALS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411444620.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-18
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Traditional alumina ceramics are prone to growth anisotropy and anisotropic grains during the preparation process, resulting in uneven microstructure and insufficient thermal conductivity, which cannot meet the heat dissipation needs of high-performance electronic devices.

Method used

Nano-scale alumina powder and micro-scale alumina fibers are used as main components, and beryllium-zirconium composite fibers are used as sintering additives to form a three-dimensional thermal conductivity network and composite solid solution to optimize the microstructure and thermal conductivity of the ceramics.

Benefits of technology

It significantly improves the thermal conductivity, mechanical properties and thermal shock resistance of alumina ceramics, and can form high-density ceramics at lower sintering temperatures, which are suitable for heat dissipation and high-temperature applications of high-performance electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005087378240000051
    Figure BDA0005087378240000051
  • Figure BDA0005087378240000061
    Figure BDA0005087378240000061
  • Figure BDA0005087378240000071
    Figure BDA0005087378240000071
Patent Text Reader

Abstract

The invention relates to the field of ceramic materials, and particularly discloses high-thermal-conductivity aluminum oxide ceramic and a preparation process thereof. The high-thermal-conductivity aluminum oxide ceramic comprises the following raw materials in parts by weight: 50-70 parts of aluminum oxide powder, 40-50 parts of aluminum oxide fibers, 8-15 parts of a sintering aid, 0.7-1.5 parts of a dispersant and 0.2-0.3 part of a binder, and the sintering aid is beryllium oxide-zirconium composite fibers. The high-thermal-conductivity aluminum oxide ceramic disclosed by the invention has excellent thermal conductivity and mechanical properties, and has an important application prospect in the field of heat dissipation of high-performance electronic devices. Besides, according to the preparation process, the sintering temperature of the aluminum oxide ceramic can be reduced, so that a more uniform and refined grain system is formed in the aluminum oxide ceramic, and the heat-conducting property of the aluminum oxide ceramic is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ceramic materials, and more specifically, to a high thermal conductivity alumina ceramic and a preparation process thereof. Background Art

[0002] Alumina ceramics are mainly composed of aluminum oxide (Al 2 O 3 ) is made according to the Al content 2 O 3 Different percentages of aluminum oxide and types of additives can produce a variety of different series of aluminum oxide materials. As an important industrial oxide ceramic material, aluminum oxide ceramics have good thermal conductivity and thermal stability, excellent mechanical properties, wear resistance and excellent corrosion resistance, making it widely used in aerospace, automotive, construction, electronics and semiconductor industries.

[0003] With the development of modern science and technology, in the field of electronic equipment, the integration and power are increasing day by day, the effective transfer of heat becomes particularly important, and the heat dissipation problem becomes particularly prominent. The thermal conductivity of traditional alumina ceramics usually cannot meet the growing heat dissipation needs of high-performance electronic devices, which limits the application of alumina ceramics in high-performance electronic devices.

[0004] With respect to the above-mentioned related technologies, the inventors found that during the preparation process of traditional alumina ceramics, they are often affected by improper additive adaptation, sintering time, temperature and other preparation processes, which leads to the occurrence of growth anisotropy and anisotropic grains in the preparation process of alumina ceramics, making the microstructure of the final alumina ceramics uneven, and even causing a high porosity inside the ceramics, resulting in a decrease in the bonding strength between the grains, making the thermal conduction path of the alumina ceramics easily interrupted, increasing thermal resistance and reducing thermal conductivity. Therefore, improving the thermal conductivity of alumina ceramics is of great significance for the application of alumina ceramics in the heat dissipation field of high-performance electronic devices, high-temperature furnaces, thermocouple protection tubes and other high-temperature application fields. Summary of the invention

[0005] In order to improve the thermal conductivity of alumina ceramics, the present application provides a high thermal conductivity alumina ceramic and a preparation process thereof.

[0006] In a first aspect, the present application provides a high thermal conductivity alumina ceramic, which adopts the following technical solution: A high thermal conductivity alumina ceramic, wherein the raw materials include 50-70 parts of alumina powder, 40-50 parts of alumina fiber, 8-15 parts of sintering aid, 0.7-1.5 parts of dispersant and 0.2-0.3 parts of binder in parts by weight, wherein the sintering aid is beryllium oxide-zirconium composite fiber.

[0007] By adopting the above technical solution, with alumina powder and alumina fiber as main components, the alumina ceramic of the present application has higher alumina purity and reduces the adverse effects of impurities on thermal conductivity.

[0008] Alumina fibers are mixed with alumina powder. On the one hand, alumina fibers can serve as a bridge for heat conduction, forming a three-dimensional heat conduction network inside the alumina powder. This network structure can form a fine-grained structure in the subsequent sintering process, optimize the internal microstructure of alumina ceramics, provide more pathways for heat diffusion, reduce phonon scattering, and reduce thermal resistance. On the other hand, alumina powder and alumina fibers fill each other, which can significantly reduce the porosity of ceramic materials, increase the density of ceramic materials, and significantly improve the thermal conductivity of alumina ceramics.

[0009] Beryllium oxide-zirconium composite fiber is used as a sintering aid. The presence of zirconium inhibits the abnormal growth of grains and can promote the formation of finer grains in the sintering process of alumina ceramics. The presence of beryllium further improves the thermal conductivity of beryllium oxide-zirconium composite fiber, thereby further optimizing the thermal conductive network formed between alumina powder and alumina fiber and improving the heat conduction efficiency.

[0010] In addition, zirconium oxide and beryllium oxide can form a composite solid solution with alumina, which reduces the energy barrier of alumina ceramics during the sintering process, further reduces the sintering temperature of alumina ceramics, improves the sintering efficiency, and can form a higher density at a lower sintering temperature, significantly improving the thermal conductivity, mechanical properties and thermal shock resistance of alumina ceramics.

[0011] Optionally, the raw materials of the beryllium oxide-zirconium composite fiber include 5-10 parts of beryllium source, 3-6 parts of zirconium source and 10-15 parts of polyvinyl alcohol in parts by weight, the beryllium source is selected from beryllium oxide, the zirconium source is selected from zirconium oxynitrate, and the beryllium oxide is in powder state.

[0012] Optionally, the preparation process of the beryllium oxide-zirconium composite fiber comprises the following steps: S1: mixing zirconium oxynitrate and nitric acid at a solid-liquid ratio of 1:(3-5) and stirring evenly, then adding beryllium oxide, and ultrasonically dispersing for 20-30 minutes to form a precursor solution; S2: adding polyvinyl alcohol to water at 50-60° C. at a material-liquid ratio of 1: (1-2.5), stirring evenly to form a substrate solution; S3: mixing the precursor solution and the substrate solution, and ultrasonically stirring for 1.5-2 hours to form a spinning solution; S4: spinning the spinning solution by electrospinning to obtain pretreated composite fibers; S5: heat-treating the pretreated composite fiber to obtain.

[0013] By adopting the above technical scheme, beryllium oxide powder is used as the beryllium source and zirconium nitrate is used as the zirconium source, a precursor solution is prepared by a sol-gel method, and then through in-situ composite method, electrospinning and heat treatment, in-situ composite of beryllium oxide and zirconium oxide is achieved, which effectively improves the interfacial bonding strength of the beryllium oxide-zirconium composite fiber and ensures the structural uniformity and performance stability of the composite fiber.

[0014] Optionally, the electrospinning conditions in step S4 are: setting the spinning positive voltage to 15-20 kV, the negative voltage to -5-1 kV, the propulsion flow rate to 0.1-0.3 mL / min, the spinneret diameter to 0.4-0.8 mm, and the distance between the syringe spinneret and the receiver to 10-15 cm.

[0015] By adopting the above technical solution, the uniformity and continuity in the fiber formation process can be effectively ensured, thereby ensuring the overall performance of the final beryllium oxide-zirconium composite fiber.

[0016] Optionally, the specific steps of the heat treatment in step S5 are: heat the pretreated composite fiber to 600-700° C. in an inert gas atmosphere, keep the temperature for 1.5-2.5 hours, and then cool to room temperature.

[0017] By adopting the above technical solution, impurities in the system can be effectively removed, zirconium oxynitrate can be decomposed to form zirconium oxide, and the interaction between beryllium oxide and zirconium oxide can be promoted to form a more stable composite structure.

[0018] Optionally, the alumina powder is α-alumina with a particle size of 100-300 nm.

[0019] Optionally, the length of the alumina fiber is 200-300 μm.

[0020] By adopting the above technical solution, micron-sized alumina fibers and nano-sized alumina powders are mixed to form a size gradient, thereby constituting a more optimized multi-sized three-dimensional heat conduction network. This multi-scale structure promotes the bridging effect of micron fibers in the nanopowder matrix, forming a continuous heat conduction path and reducing the interface resistance in heat conduction.

[0021] At the same time, nanopowders can be more fully filled into the pores between micron fibers to form a tighter microstructure, further reducing the porosity of ceramic materials. Nanoalumina powders have higher surface activity and can form more interfaces with micron fibers. These interfaces can provide more diffusion paths in the subsequent sintering process of ceramics, promote the densification of the internal structure of alumina ceramics, and significantly improve the thermal conductivity of alumina ceramics.

[0022] Optionally, the dispersant is selected from any one or more combinations of acrylate, propylene glycol methyl ether acetate, and polyvinyl pyrrolidone.

[0023] By adopting the above technical scheme, acrylate, propylene glycol methyl ether acetate and polyvinyl pyrrolidone as dispersants can effectively improve the uniform dispersion between the raw materials, help the alumina ceramics to form a denser system during the preparation process, thereby improving the overall performance of the alumina ceramics.

[0024] In a second aspect, the present application provides a preparation process of a high thermal conductivity alumina ceramic, using the following technical solution: A preparation process of a high thermal conductivity alumina ceramic, comprising the following steps: S1: mixing alumina powder with ethanol at a solid-liquid ratio of 1:(0.2-0.3), grinding for 6-8 hours, and obtaining blend A; S2: mixing alumina fiber and a sintering aid, mixing with ethanol at a solid-liquid ratio of 1:(0.2-0.3), grinding for 0.5-1h, and obtaining a blend B; S3: mixing blend A and blend B, adding a dispersant and a binder, grinding and dispersing, and obtaining a casting slurry; S4: tape-casting the tape-casting slurry, and obtaining a blank after standing and drying; S5: isostatically pressing and debinding the blank to obtain a blank, which is then hot-pressed and sintered at 750-850° C. and 200-250 MPa for 5-7 hours and cooled.

[0025] By adopting the above technical solution, ethanol is selected as the solvent, and the dispersant and binder are introduced during the mixing process, which can be quickly removed in the subsequent preparation process, thereby reducing the formation of pores and defects inside the alumina ceramics and improving the density of the alumina ceramics. It can promote the densification of ceramics and the growth of grains at a lower temperature, help eliminate pores, reduce the scattering of grain boundaries, prepare high thermal conductivity and high strength alumina ceramics, effectively improve the sintering efficiency of the product, greatly save energy consumption and equipment costs, and reduce the sintering difficulty of high thermal conductivity alumina ceramics.

[0026] Optionally, the conditions for isostatic pressing in step S5 are: firstly, the pressure of the blank is increased to 100-110 MPa, and the pressure is maintained for 1-2 min, and then the pressure is increased to 210-230 MPa, and the pressure is maintained for 4-5 min.

[0027] By adopting the above technical solution, isostatic pressing can effectively improve the density and mechanical properties of alumina ceramics, so that the prepared alumina ceramics have high thermal conductivity and excellent mechanical properties.

[0028] In summary, this application has the following beneficial effects: 1. The present application adopts nano-scale alumina powder and micron-scale alumina fiber as the main raw materials. The mutual filling between the fibers and the powder forms a special three-dimensional network conduction network with a size gradient, forming a more continuous heat conduction path inside the alumina ceramic, and significantly reducing the porosity of the alumina ceramic, reducing the generation of cracks and defects, forming a denser structure, and significantly improving the thermal conductivity and mechanical properties of the prepared alumina ceramic.

[0029] 2. The present application prepares beryllium oxide-zirconium composite fibers as a sintering aid by in-situ compounding of beryllium oxide and zirconium oxide, which can form a composite solid solution with alumina, refine the grains inside the alumina ceramics, further optimize the thermal conductivity network and microstructure inside the alumina ceramics, and effectively reduce the energy barrier of the alumina ceramics during the sintering process, so that alumina ceramics with good thermal conductivity, mechanical properties and thermal shock resistance can be obtained at a lower sintering temperature.

[0030] 3. The alumina ceramics obtained by the method of the present application have a high alumina purity, which effectively reduces the adverse effects of impurities on thermal conductivity, improves the interface bonding strength between the internal fibers and powders of the alumina ceramics, and effectively improves the thermal conductivity and mechanical properties of the alumina ceramics. DETAILED DESCRIPTION

[0031] The following examples further illustrate the present application in detail.

[0032] raw material Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples in this application are all commercially available products, specifically: Beryllium oxide, selected from Jizhi, B69330; Zirconium oxynitrate, selected from MacLean, Z820675; Zirconia, selected from McLean, Z787450; Acrylic acid ester, selected from Delun New Materials, Neocryl A-2092; Propylene glycol methyl ether acetate, selected from Delun New Materials, T108; Polyvinylpyrrolidone, selected from Huzhou Shenhua, PVP K90; The binder is hydroxypropyl methylcellulose, selected from Zhiheng Zhiyuan, HPMC-001.

[0033] Preparation Example of Beryllium Oxide-Zirconium Composite Fiber Preparation Example 1 The raw materials and amounts of beryllium oxide-zirconium composite fibers are shown in Table 1, and beryllium oxide is in powder form.

[0034] Table 1 The preparation process of the beryllium oxide-zirconium oxide comprises the following steps: S1: zirconium oxynitrate and nitric acid were mixed and stirred evenly at a solid-liquid ratio of 1:3, and then beryllium oxide was added and ultrasonically dispersed for 30 minutes to form a precursor solution; S2: adding polyvinyl alcohol to water at 60° C. at a solid-liquid ratio of 1:1.5, stirring evenly to form a substrate solution; S3: mixing the precursor solution and the substrate solution, and stirring them ultrasonically for 2 h to form a spinning solution; S4: The spinning solution is spun by electrospinning to obtain pretreated composite fibers; the spinning positive voltage is 15 kV, the negative voltage is -2 kV, the propulsion flow rate is 0.2 mL / min, the diameter of the spinneret is 0.4 mm, and the distance between the syringe spinneret and the receiver is 10 cm.

[0035] S5: The pretreated composite fiber is heated to 600° C. in an inert gas atmosphere for heat treatment, kept at this temperature for 2.5 hours, and then cooled to room temperature to obtain the result.

[0036] Preparation Example 2 The difference between the beryllium oxide-zirconium composite fiber and the preparation example 1 is that the raw materials and the amounts are as shown in Table 1, and the preparation process thereof comprises the following steps: S1: zirconium oxynitrate and nitric acid were mixed and stirred evenly at a solid-liquid ratio of 1:4, and then beryllium oxide was added and ultrasonically dispersed for 30 minutes to form a precursor solution; S2: adding polyvinyl alcohol to water at 50° C. at a solid-liquid ratio of 1:2, stirring evenly to form a substrate solution; S3: mixing the precursor solution and the substrate solution, and stirring ultrasonically for 1.5 h to form a spinning solution; S4: The spinning solution is spun by electrospinning to obtain pretreated composite fibers; the spinning positive voltage is 20 kV, the negative voltage is 1 kV, the propulsion flow rate is 0.1 mL / min, the diameter of the spinneret is 0.4 mm, and the distance between the syringe spinneret and the receiver is 12 cm.

[0037] S5: The pretreated composite fiber is heated to 700° C. in an inert gas atmosphere for heat treatment, kept at this temperature for 2 hours, and then cooled to room temperature to obtain the composite fiber.

[0038] Preparation Example 3 The difference between the beryllium oxide-zirconium composite fiber and the preparation example 1 is that the raw materials and the amounts are as shown in Table 1, and the preparation process thereof comprises the following steps: S1: zirconium oxynitrate and nitric acid were mixed and stirred evenly at a solid-liquid ratio of 1:5, and then beryllium oxide was added and ultrasonically dispersed for 20 minutes to form a precursor solution; S2: adding polyvinyl alcohol to water at 55° C. in a solid-liquid ratio of 1:1, stirring evenly to form a substrate solution; S3: mixing the precursor solution and the substrate solution, and stirring them ultrasonically for 2 h to form a spinning solution; S4: The spinning solution is spun by electrospinning to obtain pretreated composite fibers; the spinning positive voltage is 15 kV, the negative voltage is -5 kV, the propulsion flow rate is 0.3 mL / min, the diameter of the spinneret is 0.8 mm, and the distance between the syringe spinneret and the receiver is 15 cm.

[0039] S5: The pretreated composite fiber is heated to 700° C. in an inert gas atmosphere for heat treatment, kept at this temperature for 1.5 hours, and then cooled to room temperature to obtain the result.

[0040] Preparation Example 4 The difference between the beryllium oxide-zirconium composite fiber and the preparation example 1 is that the raw materials and the amounts are as shown in Table 1, and the preparation process thereof comprises the following steps: S1: zirconium oxynitrate and nitric acid were mixed and stirred evenly at a solid-liquid ratio of 1:4, and then beryllium oxide was added and ultrasonically dispersed for 20 minutes to form a precursor solution; S2: adding polyvinyl alcohol to water at 60° C. at a solid-liquid ratio of 1:2.5, stirring evenly to form a substrate solution; S3: mixing the precursor solution and the substrate solution, and stirring them ultrasonically for 2 h to form a spinning solution; S4: The spinning solution is spun by electrospinning to obtain pretreated composite fibers; the spinning positive voltage is 20 kV, the negative voltage is -3 kV, the propulsion flow rate is 0.2 mL / min, the diameter of the spinneret is 0.6 mm, and the distance between the syringe spinneret and the receiver is 12 cm.

[0041] S5: The pretreated composite fiber is heated to 650° C. in an inert gas atmosphere for heat treatment, kept at this temperature for 2 hours, and then cooled to room temperature to obtain the composite fiber. Example

[0042] Example 1 A high thermal conductivity alumina ceramic, the raw materials and amounts are shown in Table 2, wherein the alumina powder is α-alumina with a purity of ≥99% and a particle size range of 100-300nm; the length of the alumina fiber is in the range of 200-300μm and the purity is ≥99%; the sintering aid is the beryllium oxide-zirconium composite fiber prepared in Preparation Example 1; and the dispersant is selected from acrylate.

[0043] Table 2 The preparation process of the above-mentioned high thermal conductivity alumina ceramic comprises the following steps: S1: Alumina powder was mixed with ethanol at a material-liquid ratio of 1:0.2, and the mixture was added to a sand mill for sand milling for 6 hours to obtain blend A; S2: Alumina fiber and a sintering aid were mixed, and the mixture was mixed with ethanol at a material-liquid ratio of 1:0.3, and the mixture was added to a ball mill for ball milling for 0.5 hours to obtain blend B; S3: Mixing blend A and blend B, adding a dispersant and a binder, and uniformly dispersing by ball milling to obtain a casting slurry; S4: adding the casting slurry into a casting machine for casting, and then standing and drying to obtain a blank; S5: adding the blank into an isostatic press for isostatic pressing and then debinding, firstly increasing the pressure of the blank to 100 MPa, holding the pressure for 2 min, then increasing the pressure to 210 MPa, holding the pressure for 5 min, to obtain a blank; S6: hot press sintering the green block at 800°C and 250 MPa for 7 hours, and then cooling it.

[0044] Example 2 A high thermal conductivity alumina ceramic, which is different from Example 1 in that the raw materials and amounts are as shown in Table 2, and the preparation process thereof comprises the following steps: S1: mixing alumina powder with ethanol at a solid-liquid ratio of 1:0.25, adding the mixture into a sand mill and sand milling for 7 hours to obtain blend A; S2: Alumina fiber and a sintering aid are mixed, mixed with ethanol at a material-liquid ratio of 1:0.2, added into a ball mill and ball-milled for 1 h to obtain a blend B; S3: mixing blend A and blend B, adding a dispersant and a binder, grinding and dispersing, and obtaining a casting slurry; S4: adding the casting slurry into a casting machine for casting, and then standing and drying to obtain a blank; S5: adding the blank into an isostatic press for isostatic pressing and then removing the binder, firstly increasing the pressure of the blank to 110 MPa, holding the pressure for 1 min, then increasing the pressure to 230 MPa, holding the pressure for 4 min, to obtain a blank; S6: hot press sintering the green block at 750° C. and 200 MPa for 6 h, and then cooling it.

[0045] Example 3 A high thermal conductivity alumina ceramic, which is different from Example 1 in that the raw materials and amounts are as shown in Table 2, and the preparation process thereof comprises the following steps: S1: Alumina powder was mixed with ethanol at a material-liquid ratio of 1:0.3, and the mixture was added to a sand mill for sand milling for 6 hours to obtain blend A; S2: Alumina fiber and a sintering aid were mixed with ethanol at a material-liquid ratio of 1:0.25, and the mixture was added to a ball mill for ball milling for 0.5 hours to obtain blend B; S3: mixing blend A and blend B, adding a dispersant and a binder, grinding and dispersing, and obtaining a casting slurry; S4: adding the casting slurry into a casting machine for casting, and then standing and drying to obtain a blank; S5: adding the blank into an isostatic press for isostatic pressing and then debinding, firstly increasing the pressure of the blank to 100 MPa, holding the pressure for 2 min, then increasing the pressure to 230 MPa, holding the pressure for 5 min, to obtain a blank; S6: hot press sintering the green block at 850°C and 250MPa for 5h, and then cooling it.

[0046] Embodiment 4-6 A high thermal conductivity alumina ceramic, the difference between Examples 4-6 and Example 1 is that the raw materials and amounts are as shown in Table 2, and the other steps are the same as Example 1.

[0047] Example 7 A high thermal conductivity alumina ceramic, which is different from Example 1 in that the sintering aid is the beryllium oxide-zirconium composite fiber prepared in Preparation Example 2, and the other steps are the same as Example 1.

[0048] Example 8 A high thermal conductivity alumina ceramic, which is different from Example 1 in that the sintering aid is the beryllium oxide-zirconium composite fiber prepared in Preparation Example 3, and the other steps are the same as Example 1.

[0049] Example 9 A high thermal conductivity alumina ceramic, which is different from Example 1 in that the sintering aid is the beryllium oxide-zirconium composite fiber prepared in Preparation Example 4, and the other steps are the same as Example 1.

[0050] Example 10 A high thermal conductivity alumina ceramic, which is different from Example 1 in that the dispersant in the raw material is propylene glycol methyl ether acetate, and the other steps are the same as Example 1.

[0051] Embodiment 11 A high thermal conductivity alumina ceramic, which is different from Example 1 in that the dispersant in the raw material is acrylate and polyvinyl pyrrolidone in a mass ratio of 1:1, and the other steps are the same as Example 1.

[0052] Comparative Example Comparative Example 1 A high thermal conductivity alumina ceramic, which differs from Example 1 in that alumina fibers are not added, the alumina fibers in the raw materials are replaced with alumina powder of equal mass, and the other steps are the same as Example 1.

[0053] Comparative Example 2 A high thermal conductivity alumina ceramic, which differs from Example 1 in that no beryllium oxide-zirconium composite fiber is added as a sintering aid, the beryllium oxide-zirconium composite fiber in the raw material is replaced with an equal mass of alumina fiber, and the other steps are the same as Example 1.

[0054] Comparative Example 3 A high thermal conductivity alumina ceramic, which differs from Example 1 in that no beryllium oxide-zirconium composite fiber is added, the beryllium oxide-zirconium composite fiber in the raw material is replaced by zirconium oxide powder of equal mass, and the other steps are the same as Example 1.

[0055] Comparative Example 4 A high thermal conductivity alumina ceramic, which differs from Example 1 in that no beryllium oxide-zirconium composite fiber is added, the beryllium oxide-zirconium composite fiber in the raw material is replaced by an equal mass of beryllium oxide powder, and the other steps are the same as Example 1.

[0056] Performance testing The mechanical properties and thermal conductivity tests of the alumina ceramics obtained in Examples 1-11 and Comparative Examples 1-4 were carried out. Each group of tests was carried out 3 times, and the average value of the 3 tests was taken as the final result and recorded in Table 3. The relevant test standards and methods are as follows: 1. Fracture toughness: The alumina ceramics obtained in Examples 1-11 and Comparative Examples 1-4 were tested by the single-sided notched beam method (SENB method) using a WDW electronic universal testing machine, and the loading rate was set to 0.05 mm / min.

[0057] The calculation formula for fracture toughness is: KIC = Y3PLa 1 / 2 / 2bw 2 , where P is the load when the specimen breaks, N; L is the span between supports, mm; a is the depth of the specimen notch, mm; b is the width of the specimen section, mm; w is the height of the specimen section, mm.

[0058] 2. Bending strength: Referring to the method and regulations of GB / T 6569-2006, the bending strength of the alumina ceramics prepared in Examples 1-11 and Comparative Examples 1-4 was tested respectively.

[0059] 3. Density: Referring to the method and regulations of GB / T 25995-2010, the density of the alumina ceramics prepared in Examples 1-11 and Comparative Examples 1-4 was tested respectively.

[0060] 4. Thermal conductivity: Referring to the methods and regulations in GB / T 5598-2015, the alumina ceramic samples prepared in Examples 1-11 and Comparative Examples 1-4 were cut into discs with a diameter of d=10 mm, and the samples and standard samples of the same thickness were tested by a laser flash thermal diffusion coefficient tester to obtain the thermal diffusion coefficient α and specific heat Cp of the samples. The volume density of the samples was tested by the Archimedean method, and the thermal conductivity of the samples was obtained by the thermal conductivity formula λ=α·Cp·ρ.

[0061] Table 3 According to the performance test results in Table 3, it can be seen that the electrical conductivity of the high thermal conductivity alumina ceramics of the present application is ≥57.7W / (m·K) and the fracture toughness is ≥10.4MPa·m 1 / 2 The flexural strength is ≥593MPa, which not only shows excellent thermal conductivity, but also has excellent mechanical properties. This makes the high thermal conductivity alumina ceramics of the present application have broad prospects for application in high-temperature application fields such as heat dissipation of high-performance electronic devices, high-temperature furnaces and thermocouple protection tubes.

[0062] It can be seen from the performance test results of Examples 1-11 and Comparative Example 1 that the use of nano-scale alumina powder and micron-scale alumina fibers as main raw materials not only improves the purity of alumina ceramics and reduces the influence of impurities on the thermal conductivity of alumina ceramics, but also can form a special three-dimensional heat conduction network structure with a size gradient, builds a continuous heat conduction path inside the ceramic material, and the filling effect between the fibers and powders improves the density of alumina ceramics, reduces the generation of crack defects, and significantly improves the thermal conductivity and mechanical properties of alumina ceramics.

[0063] It can be seen from the performance test results of Examples 1-11 and Comparative Examples 2-4 that by in-situ compounding of zirconium oxide and beryllium oxide to prepare beryllium oxide-zirconium composite fibers as a sintering aid, the grains of alumina ceramics during the sintering process are effectively refined, the generation of abnormal grains is reduced, and the coordination with the alumina fibers further optimizes the thermal conductive network and grain arrangement built inside the alumina ceramics, reduces the sintering temperature of the alumina ceramics, forms a more stable and dense composite solid solution with alumina, and significantly improves the thermal conductivity and mechanical properties of the alumina ceramics.

[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high thermal conductivity alumina ceramic, characterized in that: In parts by weight, the raw materials include 50-70 parts of alumina powder, 40-50 parts of alumina fibers, 8-15 parts of sintering aids, 0.7-1.5 parts of dispersants and 0.2-0.3 parts of binders, and the sintering aid is beryllium oxide-zirconium composite fibers.

2. The high thermal conductivity alumina ceramic according to claim 1, characterized in that: In parts by weight, the raw materials of the beryllium oxide-zirconium composite fiber include 5-10 parts of beryllium source, 3-6 parts of zirconium source and 10-15 parts of polyvinyl alcohol, the beryllium source is selected from beryllium oxide, the zirconium source is selected from zirconium nitrate, and the beryllium oxide is in powder state.

3. The high thermal conductivity alumina ceramic according to claim 2, characterized in that: The preparation process of the beryllium oxide-zirconium composite fiber comprises the following steps: S1: mixing zirconium oxynitrate and nitric acid at a solid-liquid ratio of 1:(3-5) and stirring evenly, then adding beryllium oxide, and ultrasonically dispersing for 20-30 minutes to form a precursor solution; S2: adding polyvinyl alcohol to water at 50-60° C. at a solid-liquid ratio of 1:(1-2.5), stirring evenly to form a substrate solution; S3: mixing the precursor solution and the substrate solution, and stirring ultrasonically for 1.5-2h to form a spinning solution; S4: spinning the spinning solution by electrospinning to obtain pretreated composite fibers; S5: heat-treating the pretreated composite fiber to obtain.

4. The high thermal conductivity alumina ceramic according to claim 3, characterized in that: The conditions for electrospinning in step S4 are: setting the spinning positive voltage to 15-20 kV, the negative voltage to -5-1 kV, the propulsion flow rate to 0.1-0.3 mL / min, the diameter of the spinneret to 0.4-0.8 mm, and the distance between the syringe spinneret and the receiver to 10-15 cm.

5. The high thermal conductivity alumina ceramic according to claim 3, characterized in that: The specific steps of heat treatment in step S5 are: heat the pretreated composite fiber to 600-700° C. in an inert gas atmosphere, keep the temperature for 1.5-2.5 hours, and then cool to room temperature to obtain the composite fiber.

6. The high thermal conductivity alumina ceramic according to claim 1, characterized in that: The alumina powder is α-alumina with a particle size of 100-300nm.

7. The high thermal conductivity alumina ceramic according to claim 1, characterized in that: The length of the alumina fiber is 200-300 μm.

8. The high thermal conductivity alumina ceramic according to claim 1, characterized in that: The dispersant is selected from any one or more combinations of acrylate, propylene glycol methyl ether acetate and polyvinyl pyrrolidone.

9. A process for preparing a high thermal conductivity alumina ceramic according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: mixing alumina powder with ethanol at a solid-liquid ratio of 1:(0.2-0.3), grinding and dispersing for 6-8 hours to obtain blend A; S2: mixing alumina fiber and sintering aid, mixing with ethanol at a solid-liquid ratio of 1:(0.2-0.3), grinding and dispersing for 0.5-1h, to obtain blend B; S3: mixing blend A and blend B, adding a dispersant and a binder, grinding and dispersing, and obtaining a casting slurry; S4: tape-casting the tape-casting slurry, and obtaining a blank after standing and drying; S5: isostatically pressing and debinding the blank to obtain a blank, which is then hot-pressed and sintered at 750-850° C. and 200-250 MPa for 5-7 hours and cooled.

10. The process for preparing the high thermal conductivity alumina ceramic according to claim 9, characterized in that: The conditions for isostatic pressing in step S5 are as follows: firstly, the blank is pressurized to 100-110 MPa, maintained at the pressure for 1-2 min, and then the pressure is increased to 210-230 MPa, maintained at the pressure for 4-5 min.

Citation Information

Patent Citations

  • Alumina fiber-reinforced zirconium silicate ceramic matrix composite material and preparation method thereof

    CN104909787A

  • Sintering additive for ceramic material and preparation method thereof

    CN108752015A

  • Ceramic slurry, ceramic substrate and preparation method thereof

    CN119430877A

  • High-thermal-conductivity aluminum oxide ceramic material and new energy battery cover plate

    CN119707467A

  • Alumina ceramic composition

    EP1065190A2